Hydrolyzates from Pyropia columbina seaweed have antiplatelet aggregation, antioxidant and ACE I inhibitory peptides which maintain bioactivity after simulated gastrointestinal digestion - Cian, Raúl Esteban (2015)
The aim of this work was to evaluate the bio-accessibility of bioactive peptides with ACE I inhibition, antioxidant and antiplatelet aggregation activity obtained by enzymatic hydrolysis of Pyropia columbina proteins. Two hydrolyzates were produced (A and AF). Bio-accesibility was determined using a gastrointestinal digestion (pepsin and pancreatin) and membrane dialysis system. Hydrolyzates had peptides with medium molecular weight (2300 Da), and Asp, Glu and Ala were the most abundant amino acids. Additionally, AF presented small peptides with 287 Da. Peptides from A showed the highest angiotensin-converting enzyme activity (ACE I) inhibition by uncompetitive mechanism (IC50%, 1.2 ± 0.1 g L−1), and β-carotene bleaching inhibition. Peptides from AF presented the lower IC50% value for ABTS+• and DPPH radical inhibition, the highest copper-chelating activity (CCA), and antiplatelet aggregation activity. In vitro gastrointestinal digestion increased ABTS+• and DPPH scavenging and CCA of both hydrolyzates. Antiplatelet aggregation activity of A peptides was increased after simulated digestion process (≈157%). Peptides from both hydrolyzates were potentially bio-accessible, maintaining overall the bioactivity after gastrointestinal diges